Digitalisasi Pemilu Melalui Sistem E-Voting Guna Meningkatkan Civic Participatory Skill Mahasiswa - Salma Alifia; Dadang Sundawa (University of Muhammadiyah Malang, 2023)
This research is motivated by the new paradigm of a citizen who must have ideal competencies, one of which is civic skills. The scope of civic skills includes civic participatory skills. The aim of the research is to find out the mechanism for digitizing elections and to find out the skill level of student participation after using the digital system in general elections in university environments. The research method used is a qualitative research method with a case study approach by selecting informants using a purposive sampling technique. Then, the data used are primary data, namely data from research conducted on informants and secondary data obtained from literature studies. The results showed that by using the e-voting system the level of student political participation increased, namely in 2020 the percentage of voters was 83%, in 2021 the percentage of voters was 88% and in 2022 the percentage of voters was 91%. The presence of election digitalization using the e-voting system can improve student civic participatory skills because general elections for BEM chairmen can be carried out easily, quickly, effectively and efficiently and accurately so that there is no fraud in the vote recapitulation process.